ANALYSIS OF THE EPIZOOTIC SITUATION ON THE TERRITORY OF THE CENTRAL SECTION OF THE KYZYLKUM NATURAL PLAGUE FOCUS AT THE PRESENT STAGE - A.N. Dmitriev; A.S. Nematov; J.A. Rakhmanova (Central Asian Journal of Medicine, 2022)
Epizootological examination was carried out on the areas of the Central section of the Kyzylkum plague outbreak around the NMMC facilities. The phenomenon of depression of the number of the main plague carrier was noted, against the background of a period of gradual warming, which explains the absence of spilled plague epizootics. The existing epidemiological prerequisites provide real grounds for increasing the risks of epidemiological complications and requires constant monitoring of the state of epizootic activity in the Central Kyzylkum territory.